2009
DOI: 10.1017/s000711450999153x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent increases in heart rate variability and arterial compliance in overweight and obese adults with DHA-rich fish oil supplementation

Abstract: Heart rate (HR) variability and large arterial compliance can be improved using fish oils. DHA, a component of fish oil, has cardiovascular health benefits, but its effect on HR variability (HRV) and arterial compliance is yet to be quantified. Sixty-seven overweight or obese adults (thirty-six males and thirty-one females; 53 (SEM 2) year; BMI 31·7 (SEM 1·1) kg/m 2 ) were randomly allocated to consume either 6 g/d sunola oil (control; n 17), fish oil (260 mg DHA þ 60 mg EPA per g) at doses of 2 g/d (n 16), 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Several studies have examined the effect of fish oil supplementation on artery elasticity measured by pulse contour analysis in humans (17)(18)(19)(20)28). McVeigh et al (17) found that in nonobese individuals with type 2 diabetes, a 6-wk dietary supplementation with fish oils (3 g/d) increased C1 and C2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the effect of fish oil supplementation on artery elasticity measured by pulse contour analysis in humans (17)(18)(19)(20)28). McVeigh et al (17) found that in nonobese individuals with type 2 diabetes, a 6-wk dietary supplementation with fish oils (3 g/d) increased C1 and C2.…”
Section: Discussionmentioning
confidence: 99%
“…McVeigh et al (17) found that in nonobese individuals with type 2 diabetes, a 6-wk dietary supplementation with fish oils (3 g/d) increased C1 and C2. Wang et al (18) and Sjoberg et al (19) reported that fish oil supplementation improved C1 but had no effect on blood pressures and C2. However, 2 other studies found no effect on C1 and C2 following fish oil supplementation (20,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Several interventional studies have assessed the impact of omega-3 supplementation on vascular stiffness. Some groups reported a beneficial effect of omega-3 supplementation on vascular stiffness, [39][40][41][42] whereas others observed no effect. 43,44 Generally, these investigations were of very limited size, and large studies are lacking.…”
Section: Omega-3 Fatty Acids and Vascular Stiffnessmentioning
confidence: 99%
“…There have been numerous studies that have confirmed these earlier observations. Both clinical (Christensen et al, 1999;Villa et al, 2002;Dallongesville et al, 2003;Holguin et al, 2005;Christensen & Schmidt, 2007;Carney et al, 2010;Dai et al, 2010;Sjoberg et al, 2010;Christensen, 2011) and experimental studies (Laustiola et al, 1986;Kang & Leaf, 1994;Ayalew-Pervanchon et al, 2007;Billman et al, 2010;Mayyas et al, 2011) report that n-3 PUFA ingestion or acute intravenous administration (Billman et al, 1994) lower HR and increase HRV, suggestive of an increase in cardiac parasympathetic regulation (Billman, 2009. further report that these HR reductions and HRV increases were dose-independent (1-4 mg/kg per day for 3 months), suggesting a low threshold for this effect.…”
Section: Effect On Baseline Heart Rate and Heart Rate Variabilitymentioning
confidence: 98%